2011
DOI: 10.1007/s12529-011-9144-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Self-Rated Health and Serum Lipids Across Time

Abstract: For the men, relative to T1 SRH, an increase in T2 SRH was associated with an increase in the T3 HDL-C levels relative to T2 HDL-C and with a decrease in the T3 TRI levels relative to T2 TRI. For the women, initial changes in the SRH levels did not predict follow-up changes in either of the lipids. For both genders, the reverse causation hypothesis, expecting the T1-T2 change in each of the serum lipids to predict T2-T3 change in SRH, was not supported. For the men, there is support for the hypothesis that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…However, subjective health is a dynamic construct tending to decrease across the life span (Andersen et al, ; Letzring et al, ; Löckenhoff et al, ; Sargent‐Cox, Anstey, & Luszcz, ). Assessing these changes in subjective health is important because they have been shown to be associated with changes in the concentration of serum lipids (Shirom, Toker, Melamed, & Shapira, ), health‐related behaviors (e.g., physical activity and eating habits; Takahashi, Edmonds, Jackson, & Roberts, ), and functional health (Huxhold, Fiori, & Windsor, ; Idler & Kasl, ). Thus, identifying individuals with an increased risk toward more rapid decline on measures of subjective health might help to initiate preventive actions in time.…”
Section: Personality and Healthmentioning
confidence: 99%
“…However, subjective health is a dynamic construct tending to decrease across the life span (Andersen et al, ; Letzring et al, ; Löckenhoff et al, ; Sargent‐Cox, Anstey, & Luszcz, ). Assessing these changes in subjective health is important because they have been shown to be associated with changes in the concentration of serum lipids (Shirom, Toker, Melamed, & Shapira, ), health‐related behaviors (e.g., physical activity and eating habits; Takahashi, Edmonds, Jackson, & Roberts, ), and functional health (Huxhold, Fiori, & Windsor, ; Idler & Kasl, ). Thus, identifying individuals with an increased risk toward more rapid decline on measures of subjective health might help to initiate preventive actions in time.…”
Section: Personality and Healthmentioning
confidence: 99%
“…SAH decreased immediately after myocardial infarction (MI), increased within the first 6 weeks post-MI, and then became relatively stable (Maeland & Havik, 1988). Moreover, fluctuations in SAH corresponded to health and functioning outcomes (Deeg, Van Zonneveld, Van der Maas, & Habbema, 1989;Ferraro & Kelley-Moore, 2001;Galenkamp et al, 2013;Shirom et al, 2012). In fact, changes in SAH were found to be more predictive of mortality than baseline levels of SAH (Ferraro & Kelley-Moore, 2001;Gerber, Benyamini, Goldbourt, & Drory, 2009); and those taking place within the first weeks after a major medical event were particularly prognostic of recovery (Wilcox et al, 1996).…”
Section: Changes In Sahmentioning
confidence: 99%
“…Considerable research has shown that individuals' self-assessed health (SAH), measured on a single self-rating scale, predicts diverse health outcomes, including longevity (DeSalvo, Bloser, Reynolds, He, & Muntner, 2006;Idler & Benyamini, 1997), functional ability (Idler & Kasl, 1995;Idler, Russell, & Davis, 2000), depressive symptoms (Kosloski, Stull, Kercher, & Van Dussen, 2005), and other medical outcomes (Shirom, Toker, Melamed, & Shapira, 2012;Wang, Smith, Cumming, & Mitchell, 2006). These effects were found to be significant even after controlling for relevant covariates such as medical and socio-demographic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Post-hoc analysis showed that improved SRH coincided with weight loss and increased fruit and vegetable consumption. Of possible relevance to these observations, Shirom et al [23] found that improved SRH scores were associated with an improvement in HDL-C and triglyceride levels.…”
Section: Discussionmentioning
confidence: 89%